Three‐dimensional microfabrication of protein hydrogels via two‐photon‐excited thiol‐vinyl ester photopolymerization. Issue 22 (2nd September 2013) - Qin, Xiao‐Hua; Torgersen, Jan; Saf, Robert; Mühleder, Severin; Pucher, Niklas; Ligon, S. Clark; Holnthoner, Wolfgang; Redl, Heinz; Ovsianikov, Aleksandr; Stampfl, Jürgen; Liska, Robert
ABSTRACT Engineering three‐dimensional (3D) hydrogels with well‐defined architectures has become increasingly important for tissue engineering and basic research in biomaterials science. To fabricate 3D hydrogels with (sub)cellular‐scale features, two‐photon polymerization (2PP) shows great promise although the technique is limited by the selection of appropriate hydrogel precursors. In this study, we report the synthesis of gelatin hydrolysate vinyl esters (GH‐VE) and its copolymerization with reduced derivatives of bovine serum albumin (acting as macrothiols). Photorheology of the thiol‐ene copolymerization shows a much more rapid onset of polymerization and a higher end modulus in reference to neat GH‐VE. This allowed 2PP to provide well‐defined and stable hydrogel microstructures. Efficiency of the radical‐mediated thiol‐vinyl ester photopolymerization allows high 2PP writing speed (as high as 50 mm s−1) with low laser power (as low as 20 mW). MTT assays indicate negligible cytotoxicities of the GH‐VE macromers and of the thiol‐ene hydrogel pellets. Osteosarcoma cells seeded onto GH‐VE/BSA hydrogels with different macromer relative ratios showed a preference for hydrogels with higher percentage of GH‐VE. This can be attributed both to a favorable modulus and preferable protein environment since gelatin favors cell adhesion and albumin incurs nonspecific binding. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4799–4810